Kajian Yuridis Asas Kelestarian sebagai Dasar Pengelolaan lingkungan Hidup dalam Undang Undang Nomor 32 Tahun 2009 - Fahad Wiranata; Deni Yusup Permana (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study aims to analyze the position of the principle of sustainability and its application in environmental management. The research method used is normative juridical with a descriptive analytical approach. The results of the study indicate that the implementation of the principle of sustainability is realized through instruments such as AMDAL, UKL-UPL and SPPL, which function as preventive efforts in controlling environmental impacts. However, there are still obstacles such as limited human resources, weak supervision, low compliance of business actors and a tendency to fulfill environmental documents that are formalistic in the application of the principle of sustainability. The need to strengthen the monitoring system, increase human resource capacity and community participation so that the principle of sustainability can be implemented optimally. Thus, synergy among the government, business actors and the community is a crucial factor in achieving sustainable and environmentally conscious environmental management.